Research Article of the Poem Lady Lazarus A Study to Analyze Lady Lazarus through the Feminist Criticism Lens - Zsa Zsa Adelia Attaqiyyah; Muhammad Daffa Al Rasyid; Faldy Alhafiz Hutabarat; Habibi Fajar Simanjuntak; Piqri; T. Thyrhaya Zein (IKRA-ITH HUMANIORA : Jurnal Sosial dan Humaniora, 2026)
This study aims to analyze the poem Lady Lazarus by Sylvia Plath using a feminist critical perspective. Themain focus is on how the representation of the female body, trauma, and patriarchal power relations appearin the poem. The poem portrays a woman who repeatedly â€œresurrectsâ€ from death, symbolizing resistanceagainst social control and objectification. Therefore, this study seeks to reveal how the female voice isconstructed as a form of resistance against male dominance. The method used is a qualitative approach withtextual analysis. The data consists of the poem itself, which is examined using feminist criticism, particularlyconcepts related to the female body, objectification, and patriarchal power. The analysis is conducted byidentifying symbols, metaphors, and diction that reflect womenâ€™s experiences and their resistanceto oppressive social structures. The results show that Lady Lazarus represents a woman who is aware ofher oppression. The speaker refuses to remain a passive object and instead reclaims her body andidentity through repeated acts of â€œresurrection.â€ In conclusion, the poem not only depicts female sufferingbut also asserts female strength and agency in resisting patriarchal systems.Keywords: feminist criticism, female body, patriarchy, resistance, Sylvia Plath